Exposure to the Family Wellbeing program and associations with empowerment, health, family and cultural wellbeing outcomes for Aboriginal and Torres Strait Islander peoples: a cross-sectional analysis - Leonie Malezer Williamson; Leslie Baird; Komla Tsey; Yvonne Cadet-James; Mary Whiteside; Nadine Hunt; Raymond Lovett (BMC Public Health, 2023)
Abstract Background Empowerment is an internationally recognised concept commonly incorporated in First Nations and in this instance Aboriginal and Torres Strait Islander health and wellbeing programs. The Family Wellbeing Program is an empowerment program developed in partnership with Aboriginal and Torres Strait Islander peoples that has been widely delivered to Aboriginal and Torres Strait Islander communities across Australia for close to 30 years. To date, there has been limited quantitative analysis of how this program is linked to health and empowerment outcomes. Methods Cross sectional analysis of Mayi Kuwayu, the National Study of Aboriginal and Torres Strait Islander Wellbeing, baseline data (n = 9,843) recruited using multi-mode random sampling including mail out survey and in community convenience sampling. Logistic regression models were performed to calculate Prevalence Ratios (PRs) and 95% Confidence Intervals (CIs) to examine the association between personal control, life satisfaction, general health, family wellbeing and cultural wellbeing outcomes for Family Wellbeing participants (n = 718) versus non-participants (n = 9,125). Results Compared with non-FWB participants, FWB participants are more likely to be female (67.1% versus 58.4%), be aged 35–54 (41.8% versus 32.0%) and live in a remote area (17.7% versus 10.4%) and have educational attainment at the Year 12 level or above (57.8% versus 53.2%). Family Wellbeing participation was associated with a 13% higher reporting of family functioning, a 74% higher reporting of cultural participation and a 21% in higher reporting of local decision making in the local community compared to non-FWB participants. There were significant associations between FWB exposure compared to non-FWB exposure including reporting lower levels of health risk factors including quitting alcohol (26.4% versus 20.4%), regular exercise (67.7% versus 66.3%), quitting smoking (33.4% versus 31.9%). and e. FWB participants who had experienced both prison and youth detention ...